Teaching virtues through literature: learning from the 'Narnian Virtues' character education research. Issue 4 (1st October 2020) - Hart, Peter; Oliveira, Gisela; Pike, Mark
ABSTRACT: Character education through curriculum subjects has taken increasing political importance in England after its inclusion in the school inspection framework. Here we present a pedagogical approach to developing virtue literacy through English Literature. As part of a longitudinal, mixed-methods research project, this article uses empirical evidence from interviews with 26 students to identify and discuss the processes students used in the development of virtue literacy. The authors argue that the study of literature has a unique and valuable place in helping students develop virtue, and present areas for development in literature-based character education in the future.